Systematic review of MRI alterations in the brain following proton and photon radiation therapy: towards a uniform European Particle Therapy Network (EPTN) definition - Lauwens, Lieselotte; Ribeiro, Marvin F.; Zegers, Catharina M. L.; Høyer, Morton; Alapetite, Claire; Blomstrand, Malin; Calugaru, Valentin; Di Perri, Dario; Iannalfi, Alberto; Lütgendorf-Caucig, Carola; Paulsen, Frank; Postma, Alida A.; et al. (Radiotherapy and oncology, 2025)
Magnetic resonance imaging (MRI) often demonstrates alterations following cranial radiotherapy (RT), which may result in clinical symptoms and diagnostic uncertainty, and thus potentially impact treatment decisions. The potential differences in MRI alterations after proton and photon RT, has raised concerns regarding the relative biological effectiveness of proton therapy. To provide an overview of MRI alterations in the brain post-RT and to explore differences between photon and proton RT, a systematic review adhering to the PRISMA guidelines was conducted, focusing on the assessment methods and definitions across studies. A systematic search of three electronic databases was performed using the concepts ‘normo-fractionated radiotherapy ‘, ‘MRI alterations’ and ‘brain, skull base or head and neck tumours in adult and paediatric populations’. Data extraction and quality assessment was performed on articles meeting the predefined criteria by two independent reviewers. Out of 5887 screened studies, 94 met the inclusion criteria. These studies were categorized based on confinement of the MRI alterations to temporal lobe, brainstem, or across the entire brain. Additional subclassification was performed based on MRI sequences evaluated or by the nature of the alterations, with pseudoprogression generally reserved for glioma patients. While many papers exist on MRI alterations in the brain after RT, this review highlights significant inconsistencies in the terminology and definitions, limiting the comparability of findings across studies. Our results highlight the need for and facilitate the development of a standardized framework for describing MRI alterations after RT.
Online verfügbar 11 May 2025, Version des Artikels 14 May 2025
Gesehen am 05.11.2025